Training On Management of 3 R (Reuse, Reduce and Recycle) Coconut Waste (Cocos Nucifera L) as Planting Pots Media for Mothers in Tiwu Galih Village - Baiq Rani Dewi Wulandani; Lalu Hamzi Sofiyan Sauri; Darwin Surya Atmaja; Andreawan Husen; Rohdiatin Parihin; Susi Susanti; Windi Rosi Handayani; Liana Sapitri; Aan Ariska; Adela Novita Sinayu; Atmi Saidatin; Kania Cahyani (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Real Work Lecture (KKN) is a community service activity that involves students as participants and lecturers as supervisors that focus on the Desapreneur theme. Utilization of coconut coir waste is a product to minimize waste is the 3R. The first principle of Reduce is an activity that can reduce and prevent waste accumulation. The second principle of Reuse is the activity of reusing waste that is fit for use for the same or another function. The third principle of Recycle is the activity of processing waste into new products. In this case, Recycle is the principle that makes a new product, through coconut coir waste it will be made into a media for planting pots. Unused coir waste will have economic value and this is one part of the Desapreneur program which aims to minimize coconut coir waste in the Bogak neighborhood, Tiwu Galih Village. The implementation method is carried out using a qualitative method with implementation in the form of an initial survey as well as practical training in making products. The results issued are kokedama products or plant pot media from coconut fiber.